Product lifecycle management and compliance with international standards: a case study analysis in the footwear industry. (1st December 2014) - D'Amico, Simona; Giustiniano, Luca; Nenni, Maria Elena; Pirolo, Luca
As the globalisation of markets in the footwear industry became more evident, several restrictions have been imposed by international directives, standards and regulations, as well as by market requirements. Such external needs are progressively pushing the footwear manufacturers to introduce continuous improvements in their production processes and in the firm management in general. The aim of this paper is to evaluate the awareness of the adoption of product lifecycle management (PLM) in the fashion industry, in order to describe the state of the art in the Italian context. To this extent, we investigated the conformity to industry-related technical regulations as a first step towards the international development of companies. The paper presents the preliminary results of a survey conducted in the Riviera del Brenta industrial district in the Veneto Region of Italy.